Early diagnostic indicators of dengue versus other febrile illnesses in Asia and Latin America (IDAMS study): a multicentre, prospective, observational study - Rosenberger, Kerstin; Tobian, Frank; Sarker, Malabika; Jänisch, Thomas; Beck, Dorothea; Gaczkowski, Roger; Junghanss, Thomas; Morales, Ivonne; Wirths, Marius (The lancet. Global health, 2023)
Improvements in the early diagnosis of dengue are urgently needed, especially in resource-limited settings where the distinction between dengue and other febrile illnesses is crucial for patient management.